Keanekaragaman dan Kelimpahan Makrozoobentos di Sungai Naborsahan Kabupaten Toba Samosir Sumatera Utara - Melinda Sari Lubis; Mohammad Basyuni; Ani Suryanti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2013)
This research described diversity and abundance of macrozoobenthos in Naborsahan River Toba Samosir Regency of North Sumatra. Macrozoobenthos sampling station consists of 3 stations using purposive random sampling method. Physical and chemical parameters were measured as temperature, currents, depth, brightness, turbidity, organic content on C-substrate, pH, DO, and BOD5. Macrozoobenthos obtained 5 phylum, i.e. Annelida, Arthropoda, Nemertea, molluscs and Platyhelminthes which were divided into 26 genera. First station had a value diversity index (H') of 2,25 with a high of 11 genera. Tryonia genera had the highest value abundance of 14.430 ind/m2 that found at third station.Keywords: Diversity, Abundance, Macrozoobenthos, Naborsahan.